STRATEGI METAKOGNITIF DALAM PEMBELAJARAN MATEMATIKA DAN DAMPAKNYA TERHADAP PENALARAN MATEMATIS SISWA: SYSTEMATIC LITERATURE REVIEW - Ni Nyoman Lena Adisaraswathi; I Gst Putu Sudiarta; Gede Suwekan; Gst. Ayu Mahayukti; Ni Made Sri Mertasari (Universitas Muria Kudus, 2026)
This article examines the influence of metacognitive strategies in mathematics learning, particularly on students’ mathematical reasoning ability, through a Systematic Literature Review (SLR) approach guided by the PRISMA framework, consisting of identification, screening, eligibility, and inclusion stages. The data were obtained from scientific articles published between 2020-2026 through Google Scholar, Publish or Perish, and ResearchGate. In the identification stage, 673 articles were initially retrieved. These articles were then selected based on predetermined inclusion and exclusion criteria, including their relevance to metacognitive strategies in mathematics learning, their connection to mathematical ability or mathematical reasoning, the publication year range, and the availability of full-text articles. After the screening and eligibility assessment processes, 21 articles were selected for further analysis. The data were analyzed by reviewing, categorizing, and synthesizing the findings from the relevant studies. The results indicate that metacognitive strategies have a positive impact on mathematics learning by assisting students in planning problem-solving procedures, monitoring their thinking processes, and evaluating their answers. These strategies also contribute to the improvement of students’ mathematical reasoning ability, as reflected in their capacity to understand problems, construct arguments, connect mathematical concepts, examine solution steps, and draw logical conclusions. The effectiveness of metacognitive strategies is influenced by several factors, including students’ prior ability, mathematics anxiety, self-regulated learning, and support from the learning environment. With appropriate implementation, metacognitive strategies can serve as an effective instructional alternative for developing students’ mathematical abilities, particularly mathematical reasoning.